KEPUASAN KONSUMEN TERHADAP FASILITAS DI KARANG RESTAURANT KTM RESORT BATAM - Melani, Andi; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research was conducted to know the facilities contained in karang restaurant KTM resort Batam and to know customer satisfaction with facilities in karang restaurant KTM resort Batam. The research method used is quantitative approach. The sample technique used is accidental sampling. Samples taken as many as 100 respondents, taken into the research respondents are the guests who come to karang restaurant with a view to knowing expectations before using the facility and reality after using the facility. The data were collected using, interview, observation, and questionnaire. Analysis of data use is done by comparing expectations and reality of the responses of respondents. The results of the research indicate the reality is higher than the expectation so that overall cunsumers feel less satisfied with the facilities contained in karang restaurant KTM resort Bata (y>x).Keywords: Customer satisfaction, Facilities, Level of Conformity